Monitoring Alat Ukur Kecepatan Arus Air Laut Berbasis Internet of Things (IoT) - Muhammad Nur Wahid Barokah; Ageng Ibnu Sahrial; Yudhi Yudhi; Valentin Vina Ratnapuri (Jurnal Inovasi Teknologi Terapan, 2026)
Abstract This final study focuses on the development of a sea current speed measuring device designed using Internet of Things (IoT) technology, allowing it to be monitored in real-time via mobile devices. The system integrates several core components, including the ESP32 microcontroller, the LM393 infrared speed sensor, and a disk encoder. It utilizes MIT App Inventor as the interface between the device and the user. The sea current speed data is displayed in RPM and cm/s units, both on an LCD screen and within an Android application. Device testing was conducted over three consecutive days at three different locations to evaluate system performance under real-world environmental conditions. The results showed that the system was capable of delivering accurate data readings, with an average accuracy rate of 93,09%. With these capabilities, the system is expected to provide a practical, affordable, and efficient solution for monitoring sea current speeds, particularly for fishermen and other users who require direct and continuous oceanographic data